Sheep grazing in 'lawnscape' management: an emissions comparison with conventional 'lawnscape' management. (16th November 2016) - Lenaghan, Michael Alexander
Abstract: The use of sheep in lawnscape management is touted as a low-carbon alternative to conventional lawnscaping; however this claim remains unsubstantiated. While conventional lawnscaping generates greenhouse gas (GHG) emissions, primarily through fuel combustion, sheep grazing produces methane (CH4 ) as well as manure which releases embodied nitrogen as nitrous oxide (N2 O) as it degrades. These gases have a carbon equivalency of 25 and 298 respectively, indicating their much greater potency as GHGs relative to carbon dioxide (CO2 ). This paper is the first to critically profile and compare GHG emissions produced by grazing and conventional lawnscape management. It discusses critical factors affecting the carbon footprint of both practices, and develops a framework for evaluating lawnscape management emissions. This study finds that replacing lawnmowers and the treatment and application of compost with a grazing regime can reduce net lawnscape management emissions by 34–37%, or 980 kgCO2 e/ha/year.